“Ynclinando la oreja del mi entendimiento”. Mystic Symbolism in Teresa de Cartagena’s Arboleda de los enfermos - Ilse Díaz Márquez (Medievalia)
Arboleda de los enfermos is a religious treaty written in the middle of 15th century by Teresa de Cartagena, a nun from Burgos, after her hearing loss. In her treaty, Teresa de Cartagena attemps to show to those who also suffer from an illnes a way to heal their souls. The text presents some characteristics of mystic Spanish literature, as it exposes the comprehension process of an inner reality in wich the soul needs to follow a crucial path of suffering. This paper analizes the symbolism in the treaty, from the Scholem and Lotman’s perspectives about the symbol as a vehicle of tradition and mystical experience, to later explain the relationship between symbols of the Christian and Jewish traditions presented on the text. Teresa de Cartagena could have known this second tradition due to the Jewish converso origins of her family, in wich her grandfather, the ex rabine Pablo de Santa María, and her uncle Alfonso de Cartagena were counted, both prominet humanist and educated in Hebrew tradition.